Are Corn Futures Prices Getting "Jumpy"?. Issue 2 (10th January 2020) - Couleau, Anabelle; Serra, Teresa; Garcia, Philip
Abstract : The article sheds light on price jump risk in corn futures prices in the era of electronic trading and after the shift to real‐time announcement of USDA reports. Using intraday prices from 2008 to 2015, we employ a nonparametric test to detect jumps and variance analysis to assess the relative importance of jump risk. Real‐time trading of major USDA reports has substantially increased the frequency and clustering of price jumps, and results in higher market liquidity costs. In contrast, although the presence of jumps on non‐announcement days has doubled recently, their magnitude has declined as have transactions costs during their occurrence. The largest jump risk or execution risk is experienced by high frequency traders due to heightened microstructure noise during price jumps. However, traders holding long‐term market positions are only minimally affected by increased jump risk.